Climate change vulnerability and resilience of urban poor in Khulna, Bangladesh: the role of asset-based community development approach. Issue 2 (4th May 2021) - Hossain, Md. Zakir; Rahman, Md. Mostafizur
ABSTRACT: This article explores how the asset-based community development approach has improved the living conditions of the urban slum communities and have also addressed the house level poverty through direct asset transfer that can have positive co-benefits for community resilience to climate change. A broader and less restrictive design, which is qualitative in nature, has been adopted to produce arguments using the experiences of the members of Community Development Committees (CDCs) of slums of Khulna city. Considering the great flexibility nature of open-ended interview data, thematic analysis has been applied to identify and interpret the patterns (themes) related to the activities of CDCs. The findings of the aggregated thematic data show that while community-driven actions might not be taken with climate change adaptation specifically in mind, local community-based actions initiated by the CDCs of slums such as community-driven slum upgrading and collective savings schemes to reduce asset erosion directly contribute to broader resilience to climate change, by reducing exposure to climatic risk and also addressing internal drivers of vulnerability. The findings of capacity-decision-making matrix show that the CDC members do not possess equal capacity while managing the vulnerability through transferring the asset both at household and community level.